Dedifferentiated chordoid meningioma with rhabdomyosarcomatous differentiation on the middle cranial fossa. Issue 6 (16th May 2016) - Fudaba, Hirotaka; Abe, Tatsuya; Morishige, Masaki; Momii, Yasutomo; Kashima, Kenji; Yamada, Akira; Nagatomi, Hirofumi; Natsume, Atsushi; Hirato, Junko; Nakazato, Yoichi; Fujiki, Minoru
Abstract : A 46‐year‐old woman presented with headache and right hemiparesis. MRI demonstrated a mass in the left middle fossa. Total resection was performed. A histological examination of the tumor specimen showed several characteristic morphological features. A chordoid meningioma showing an epithelial‐like palisade arrangement was observed. An anaplastic short spindle cell tumor exhibiting a fascicular pattern was considered to be a rhabdomyosarcoma. After conventional radiotherapy, the tumor was well controlled without any neurological deficit for 20 months. When subsequent recurrences were observed, the patient was treated by surgery, stereotactic radiosurgery and chemotherapy. Thirty‐two months after the initial treatment, the patient died due to intracranial dissemination and an autopsy was performed. The histological examination of the recurrent and autopsy specimens showed a prominent sarcoma component. This case appears to be the first reported intracranial tumor diagnosed as a dedifferentiated chordoid meningioma with rhabdomyosarcomatous differentiation.